Association of Immune‐Related Adverse Events with Clinical Benefit in Patients with Advanced Non‐Small‐Cell Lung Cancer Treated with Nivolumab. (22nd June 2018) - Toi, Yukihiro; Sugawara, Shunichi; Kawashima, Yosuke; Aiba, Tomoiki; Kawana, Sachiko; Saito, Ryohei; Tsurumi, Kyoji; Suzuki, Kana; Shimizu, Hisashi; Sugisaka, Jun; Ono, Hirotaka; Domeki, Yutaka; et al.
Abstract: Background: Immune‐related adverse events (irAEs) are frequently observed with nivolumab monotherapy. This study aimed to evaluate whether the development of irAEs correlates with treatment response in advanced non‐small‐cell lung cancer (NSCLC). Patients and Methods: We conducted a retrospective study of patients who received nivolumab monotherapy at Sendai Kousei Hospital ( n  = 70). The patients were categorized into two groups based on the incidence of irAEs: those with irAEs (irAE group) or those without (non‐irAE group). Treatment efficacy was evaluated in each group. The patients were further categorized into responders and nonresponders, and predictive factors of treatment response were determined. Results: The objective response rate was 57% in the irAE group versus 12% in the non‐irAE group. Median progression‐free survival was 12.0 months in the irAE versus 3.6 months in the non‐irAE group. The incidence of both irAEs and pre‐existing antithyroid antibody was significantly higher in responders than in nonresponders. Multivariate analysis identified incidence of irAEs and pre‐existing antithyroid antibody as an independent predictor of treatment response. Conclusion: Objective response rate and progression‐free survival were significantly better in the irAE than in the non‐irAE group in patients with advanced NSCLC treated with nivolumab monotherapy. The development of irAEs was associated with clinical efficacy, and the presence of pre‐existing antithyroid antibody might be correlated with treatment response to nivolumab monotherapy. Implications for Practice: Immune‐related adverse events (irAEs) are frequently observed with nivolumab monotherapy. This study evaluted whether the development of irAEs correlates with treatment response in advanced non‐small‐cell lung cancer. Results showed that the objective response rate and progression‐free survival were significantly better in the patients who developed irAEs than in the patients who did not develop irAEs, and the incidence of irAEs and positivity for antithyroid antibody at pretreatment were independent predictors of treatment response of nivolumab monotherapy. Therefore, the development of irAEs predicts clinical benefit and suggests that cautious management of irAEs can lead to achieving maximum clinical benefit from nivolumab monotherapy. Abstract : This article reports the results of a study evaluating the development of immune‐related adverse events in patients who received nivolumab monotherapy to determine clinical benefit in patients with advanced non‐small cell lung cancer.